PERANCANGAN INDOOR MULTIFUNCTION STADIUM DENGAN ARSITEKTUR HIGH-TECH DI SAMPORA, KABUPATEN TANGERANG - Utami, Widya Laras Ning; Sulistyowati, Anggraeni Dyah; Suryandari, Putri (MAESTRO, 2024)
Sports and arts, especially music, have an important role in human life. Sports is one of the recreational facilities for both children, teenagers and parents. Music concerts have a big role in promoting Indonesia to the world community. Indirectly, this makes music concerts one of the driving factors for the revival of the national economy in the future. Currently, the Indonesian National Sports Committee (KONI) of Tangerang Regency oversees 58 sports, 55 parent sports and 3 functional organizations, and coordinates 29 sub-district coordinators in Tangerang Regency. With the achievements of the existing sports in Tangerang Regency, but until now the facilities provided by the Tangerang Regency government are still inadequate. This can have an impact on athletes so that it affects the achievements of Tangerang Regency sports and the comfort of the audience in the stands which is less than optimal. This Indoor Multifuction Stadium is designed and will make the Indoor Multifunction Stadium a place that is able to accommodate activities for activities and foster sports achievements in Tangerang Regency, especially Handball, Basketball, Futsal, Volleyball and also as a place for community entertainment activities. In addition, this Indoor Multifunction Stadium will make the icon of Tangerang Regency. The concept taken in the design of Indoor Multifunction Stadium is the High Tech approach. High-Tech architecture will create the flexibility of the building towards its activities.